2019
DOI: 10.1039/c9sc03840j
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific C-terminal dinitrophenylation to reconstitute the antibody Fc functions for nanobodies

Abstract: A practical strategy to reconstitute the Fc functions of nanobody was developed by nanobody C-terminal dinitrophenylation. The Fc functions are successfully reinstated as proved by the potent ADCC and CDC in vitro and anti-tumor efficacies in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…7 , the half-life of 7D12-ZZ and ZZ-7D12 could reach 25.9 and 29.5 h, respectively, which were approximately 160.9- and 183.4-fold improved compared to the previously reported 0.16 h half-life of 7D12. 28 Additionally, no significant difference in half-life was observed between 7D12-ZZ and ZZ-7D12. The significant improvement of the pharmacokinetics of UEAR Nbs could be attributed to the in situ formed immune complex of the ZZ domain with endogenous IgGs, whose sizes were increased to above the renal threshold, thereby avoiding waste-pass clearance.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…7 , the half-life of 7D12-ZZ and ZZ-7D12 could reach 25.9 and 29.5 h, respectively, which were approximately 160.9- and 183.4-fold improved compared to the previously reported 0.16 h half-life of 7D12. 28 Additionally, no significant difference in half-life was observed between 7D12-ZZ and ZZ-7D12. The significant improvement of the pharmacokinetics of UEAR Nbs could be attributed to the in situ formed immune complex of the ZZ domain with endogenous IgGs, whose sizes were increased to above the renal threshold, thereby avoiding waste-pass clearance.…”
Section: Resultsmentioning
confidence: 93%
“…27 For example, we and others demonstrated that nanobody-DNP conjugates could form an in situ immune-complex with specific endogenous anti-DNP antibody existing in human serum and subsequently provoke potent ADCC and CDC cytotoxicity to target destructing cancer cells in vitro and exhibit in vivo antitumor activity in mouse xenograft models. 28,29 Notably, it is observed that the pharmacokinetic profile of nanobody-DNP conjugates was improved more than 20-fold in the presence of anti-DNP antibodies. 28 This strategy provides a novel and effective solution to reconstitute the missed Fc-mediated anticancer biological function and extend the half-life of nanobody simultaneously, which could potentially avoid the adverse immunogenicity issues associated with nanobody-Fc fusion protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] For example, we demonstrated that nanobody-based ARMs could efficiently recognize cancer cells and trigger ADCC and CDC immune activities to eliminate cancer cells in vitro and in vivo. [15] Recently, to further magnify the antibody recruiting capability of ARMs for enhanced immune activity, novel chemical entity that include multiple haptens in ARMs were explored for cancer immunotherapy. [16] Liposomes decorated with folic acid and Rha were developed to target folate receptor expressing cancer cells and induce cancer cell death in CDC mechanism in the presence of anti-Rha antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Human EGFR‐targeting nanobody 7D12 containing a myc tag, sortase recognition sites, and a 6 × His tag was expressed in Escherichia coli as we reported previously. [ 30 ] Then, nanobody 7D12 and DBCO‐triglycine 5 were mixed in reaction buffer (50 m m Tris/HCl, 150 m m NaCl, 5 m m CaCl 2 , pH = 7.5) in the presence of the enzyme SrtA at 16 °C. Under these conditions, SrtA could recognize the pentapeptide LPETG at the C‐terminus of nanobody 7D12 and cleave the amide bond between T and G to form a 7D12‐SrtA intermediate, which could further react with DBCO‐triglycine 5 to generate DBCO‐7D12 conjugate 6.…”
Section: Resultsmentioning
confidence: 99%